SPIRITUAL PASIEN PALIATIF DI RUMAH SAKIT, YOGYAKARTA SPIRITUALITY OF PALLIATIVE PATIENT IN HOSPITAL, YOGYAKARTA Milatul - Milatul Afifah; Arianti (Universitas Jenderal Achmad Yani Yogyakarta, 2018)
Background: Palliative care goal is to improve the quality of life of the patient. Spiritual is believed can improve the quality of life in palliative patients. Objective: The purpose of this research is to identify the spiritual status of palliative patients in PKU Muhammadiyah Gamping Yogyakarta Hospital. Methods: This study is a non-experiment research. It used descriptive survey research method with 100 subjects which used total sampling technique. FACIT-Sp is choosen based on this validity(r=0,5) dan realibity (r=0,768) to get the spiritual status of the sample. Results: The result of univariate analysis showed that the spiritual level of palliative patients in PKU Muhammadiyah Gamping Hospital with the mean values of 36,79 (0-48) and the spiritual component consisted of mean is 12,26 (0-16), faith is 12,85 (0-16) and peace 68 (0-16). Conclusion: The spiritual status of palliative patients at Muhammadiyah Gamping Yogyakarta Hospital in the categories of meaning, faith, peace and spiritual level most have passed the cut of point, it showed that the palliative patient is headed to the good spiritual. Keyword : Palliative care, spiritual, mean, faith, peace